Pola Komunikasi Kepala Desa dalam Meningkatkan Partisipasi Masyarakat pada Perencanan Pembangunan di Desa Kaju Wangi Kecamatan Elar Kabupaten Manggarai Timur - Timotius Supardi; Imam Mukti; Ismail Ismail (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2025)
Communication Pattern of Village Head in Increasing Community Participation in Development Planning in Kaju Wangi Village, Elar District, East Manggarai Regency is an effort to improve the quality of life and life for the greatest welfare of the people of Kaju Wangi Village. The purpose of this study is to determine the Communication Pattern of Village Head in Increasing Community Participation in Development Planning in Kaju Wangi Village, Elar District, East Manggarai Regency. And what are the supporting and inhibiting factors. The method used in this study is qualitative, using data collection techniques, namely observation, interviews and documentation. Based on the results of research in the field, it was obtained that the Communication Pattern of Village Head in Increasing Community Participation in Development Planning in Kaju Wangi Village, Elar District, East Manggarai Regency was not optimal because it was seen from several planning participation programs. The implementation of infrastructure development by the Kaju Wangi Village government was still not enough to implement programs that had not been realized, then the facilities and infrastructure provided by the infrastructure development implementation planning participation program. In addition, there is also a factor of lack of community involvement in the participation program for planning the implementation of development in Kaju Wangi Village because the community prioritizes their own activities.